PENGARUH KELOMPOK REFERENSI, MOTIF EKONOMI DAN PENDIDIKAN KEWIRAUSAHAAN DI SEKOLAH TERHADAP INTENSI BERWIRAUSAHA SISWA SMK DI KOTA MALANG - Patrikha, Finisica Dwijayati (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study aimed to determine the intentions for entrepreneurship by the vocational school students in the Malang city which are affected by the reference group, economic motives and entrepreneurship education in schools. Respondents are 261 students. Data were collected by mixed-method approach, which means quantitative data by regression analysis incorporating with qualitative data by indepth interviews. These results indicate that the reference group and entrepreneurship education positively affects students' entrepreneurial intentions. Variable economic motives have a strong influence on the intentions of entrepreneurship, the motive to fullfil their needs, to earn profit, to get the award, to gain power, and social motives, and motive to provide better condition for the family becomes the basic reason for students to choose entrepreneur as their career choice. However, students are still difficult to identify the steps that must be taken to start a business